Association of dietary patterns with anxiety, depression, and stress in patients with type 2 diabetes: a cross-sectional study - Sajedeh sadat moghaddam; Fateme Cheshmi; Narges Shahnazi; Poorya Basafa-Roodi; Mohammad Hasan Sohouli; Marzie Zilaee (Diabetes Epidemiology and Management)
Background: psychiatric problems such as depression, anxiety, and stress are common among patients with type 2 diabetes. Dietary patterns are more likely to have an essential role in the control of diabetes and its complications. Objective: This study was conducted to assess the associations between dietary patterns with psychological parameters, and fasting blood sugar in patients with type 2 diabetes mellitus. Methods: This cross-sectional study involved 419 men and women with type 2 diabetes aged between 25–50 years old from five health centers in Arak City, Iran. Anthropometric indices and fasting blood sugar were measured and a 168-item food frequency questionnaire (FFQ) was collected for the extraction of main dietary patterns. Result: We found that adhering to a healthy dietary pattern was associated with a lower risk to stress (odds ratio: 0.31, 95% confidence interval: 0.13-0.72 P-trend= 0.002) while adhering to a western dietary pattern linked to higher fasting blood glucose (odds ratio: 2.25, 95% confidence interval: 1.00-5.06 P-trend= 0.039) after taking into account for confounding factors by ANCOVA. We found no significant correlation between the dietary patterns and both anxiety and depression. Conclusion: It seems that in patients with type 2 diabetes, following a healthy dietary pattern is more likely to inversely associated with the risk of stress and hyperglycemia.